Comparison of the Realization of Investment Flows and Disaster Risks on the Economy of Sumatra and Java Islands in Indonesia - Febrianto Wibowo; Marselina Djayasinga; Neli Aida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Investment is still included in the important macroeconomic model of the region in helping to smoothen the movement of the economy, while the disaster risk side plays a role in seeing how it impacts the economic rate of a region. This study focuses on looking at the comparison of investment conditions and disaster risk on 2 major islands in Indonesia, namely the islands of Sumatra and Java on economic growth. Secondary data is used in the form of panel data, using multiple linear regression analysis tools. The area used includes 10 provinces on the island of Sumatra and 6 provinces on the island of Java in the 2015-2020 time series. The results of the study explain that the model on the islands of Sumatra and Java has a significant positive effect and the disaster risk index has a significant negative effect on economic growth. Investments in the islands of Sumatra and Java are very helpful in spurring the economy of each province, while disaster risk is a negative threat to the economy of the two islands.